The Effect of Technopreneurial Self-Efficacy on Technopreneurship Intention: The Moderating Role of Technopreneurial Motivation - Saady, Farma Ladia; Kurjono, K; Mulyani, Heni (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study examines the effect of technopreneurial self-efficacy (TSE) on technopreneurship intention (TI) among non-engineering university students, with technopreneurial motivation (TM) as a moderating variable. Grounded in the Theory of Planned Behavior, TSE reflects perceived behavioral control, while TM functions as a motivational driver that can strengthen intention formation. A quantitative survey was conducted with 224 non-engineering undergraduates at Universitas Pendidikan Indonesia who had completed at least one entrepreneurship-related course. Data were collected via an online questionnaire using validated measurement scales and analyzed through Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that TSE has a significant positive effect on TI (p < 0.001), TM positively influences TI (p < 0.001), and TM significantly moderates the TSE-TI relationship (p = 0.014), although with a small effect size. The model accounts for 65.9% of the variance in TI, emphasizing the combined influence of capability beliefs and motivational forces on technopreneurial intentions. These findings extend the Theory of Planned Behavior by integrating a motivational construct into the prediction of technology-based entrepreneurial intention, particularly within the underexplored context of non-technical students. The study recommends that higher education institutions adopt integrative interventions—such as experiential learning, mentoring, and digital business simulations—to concurrently strengthen self-efficacy and nurture intrinsic motivation, thereby fostering a more inclusive and innovative technopreneurship ecosystem.